2017
DOI: 10.1111/1365-2745.12876
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling competitive vs. climatic drivers of tropical forest mortality

Abstract: Tropical forest mortality is controlled by both biotic and abiotic processes, but how these processes interact to determine forest structure is not well understood. Using long‐term demography data from permanent forest plots at the Paracou Tropical Forest Research Station in French Guiana, we analysed the relative influence of competition and climate on tree mortality. We found that self‐thinning is evident at the stand level, and is associated with clumped mortality at smaller scales (<2 m) and regular spacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 110 publications
(180 reference statements)
4
25
1
Order By: Relevance
“…Previous studies have shown that higher temperatures coupled with stronger water deficit, whether in the form of low precipitation or extended dry seasons or both, are well-known drivers of tree mortality [ 73 75 ]. Our results corroborate other studies (e.g., [ 29 , 76 ]) and show that the highest rates of tree mortality were found in the two regions with the strongest water deficit, namely coastal dry forests in Eastern Venezuela and Western Plains ( Table 2 ). The case of recruitment is less clear since sites with higher water availability (e.g., Central Amazon) also had high recruitment rates (mean of 2.41% year -1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that higher temperatures coupled with stronger water deficit, whether in the form of low precipitation or extended dry seasons or both, are well-known drivers of tree mortality [ 73 75 ]. Our results corroborate other studies (e.g., [ 29 , 76 ]) and show that the highest rates of tree mortality were found in the two regions with the strongest water deficit, namely coastal dry forests in Eastern Venezuela and Western Plains ( Table 2 ). The case of recruitment is less clear since sites with higher water availability (e.g., Central Amazon) also had high recruitment rates (mean of 2.41% year -1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Norby et al, 2016) to determine whether a change in seedling assimilation rates is likely to lead to a vegetation composition shift, thus affecting τ via MP mechanisms. Second, recruitment of new tree cohorts is strongly affected by the light and moisture environment at the forest floor (Muscolo et al, 2014;Poorter et al, 2019).…”
Section: Response Of τ To Environmental Change -Pft Establishment Ratmentioning
confidence: 99%
“…In that respect, the species identity is far less important than the functional signature of the species assemblage (Kunstler et al 2016): for example, an assemblage of lightdemanding species will respond differently to disturbance from an assemblage of shade-tolerant understorey species . Structural characteristics of the pre-disturbance species community (stem density, average size, live biomass and so on) may also be of primary importance because they are core indicators of the silvigenetic stage of the forest (Pillet et al 2017).…”
Section: Introductionmentioning
confidence: 99%